Manufacturing method for RTQ sintered magnets
The method controls boron and carbon content in the R-T-Q sintered magnet manufacturing process to enhance coercive force and residual magnetic flux density by adjusting hydrogen content and particle size, addressing the challenges of heavy rare earth element scarcity and carbon incorporation.
Patent Information
- Application Number
- JP2024559717
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2023-02-24
- Filing Date
- 2024-02-13
- Publication Date
- 2024-12-24
- Estimated Expiration
- 2044-02-13
AI Technical Summary
Existing R-T-B sintered magnets face challenges in maintaining high coercive force (HcJ) at high temperatures due to irreversible thermal demagnetization, while reducing the content of heavy rare earth elements like Dy, which are scarce and costly, and the incorporation of carbon (C) increases during the manufacturing process, affecting grain boundary thickness and magnetic properties.
A manufacturing method that controls the thickness of the two-grain grain boundary by adjusting the amounts of boron (B) and carbon (C) within specific ranges, involving hydrogen pulverization and fine pulverization steps to produce alloy powder with controlled hydrogen content and particle size, followed by sintering to form an R-T-Q based sintered magnet.
The method enables the production of R-T-Q sintered magnets with enhanced coercive force (HcJ) and residual magnetic flux density (Br) by suppressing the increase in carbon content, even at reduced powder particle sizes, thereby improving magnetic properties without relying heavily on heavy rare earth elements.
Smart Images

Figure 0007605387000001 
Figure 0007605387000002 
Figure 0007605387000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for producing an RTQ sintered magnet. [Background technology]
[0002] RTB sintered magnets (R is at least one rare earth element. T is at least one transition metal element, always including Fe. B is boron) are known as the most high-performance magnets among permanent magnets, and are used in a variety of motors, including electric vehicle motors (EV, HV, PHV, etc.), industrial equipment motors, and home appliances. RTB sintered magnets are mainly R2T 14 It is composed of a main phase made of B compounds and a grain boundary phase (hereinafter sometimes simply referred to as "grain boundary") located at the grain boundary portion of this main phase. 14 The B compound is a ferromagnetic phase with high magnetization.
[0003] RTB sintered magnets have a coercive force H cJ (Hereinafter, simply "coercive force" or "H cJ This causes a problem of irreversible thermal demagnetization, as the magnetization temperature drops and the magnetization rate drops. Therefore, RTQ sintered magnets, which are used in electric vehicle motors in particular, have a high H cJ It is required that the applicant have:
[0004] In RTB sintered magnets, R2T 14 When a part of the light rare earth elements (mainly Nd and / or Pr) contained in R in the B compound is replaced with heavy rare earth elements (mainly Dy and / or Tb), H cJ It is known that the H cJ will improve.
[0005] However, R2T 14 When the light rare earth elements in the B compound are replaced with heavy rare earth elements, the H of the RTB sintered magnet cJ While the residual magnetic flux density B r (Hereinafter, simply "B rIn addition, heavy rare earth elements, especially Dy, are scarce and have limited production areas, so their supply is unstable and their prices fluctuate greatly. For this reason, in recent years, users have been promoting the use of H as little as possible without using heavy rare earth elements. cJ There is a need to improve this.
[0006] Patent Document 1 discloses an RTQ rare earth sintered magnet with increased coercivity while reducing the Dy content. The composition of this sintered magnet is limited to a specific range in which the amount of B is relatively small compared to commonly used RTQ alloys, and contains one or more metal elements selected from Al, Ga, and Cu. As a result, R2T is formed at the grain boundaries. 17 Phase is generated and this R2T 17 Transition metal-rich phase (R6T 13 As the volume ratio of H cJ will improve. [Prior art documents] [Patent documents]
[0007] [Patent Document 1] International Publication No. 2013 / 008756 Summary of the Invention [Problem to be solved by the invention]
[0008] High B while reducing the content of heavy rare earth elements r and high H cJ In order to realize an RTQ sintered magnet with this property, technology is being investigated to control the thickness of the two-particle grain boundary by relatively reducing the amount of B (boron concentration). However, it has been found that in order to thicken the two-particle grain boundary, it is necessary to reduce not only the amount of B but also the amount of C. This is because C can partially substitute for B in the main phase and function in the same way as B. Below, B and C will be collectively represented as Q, and "RTB sintered magnets" may be referred to as "RTQ sintered magnets".
[0009] On the other hand, it was also found that reducing the particle size of the powder particles (powder grain size) increases the amount of carbon incorporated into the magnet powder during the manufacturing process, resulting in an increase in the amount of C in the sintered magnet. For this reason, when the powder grain size is reduced, it is necessary to suppress the increase in the amount of C during the manufacturing process.
[0010] The method for producing an RTQ sintered magnet according to the present disclosure makes it possible to suppress an increase in the C content even when the powder particle size is reduced. [Means for solving the problem]
[0011] In a non-limiting exemplary embodiment, a method for producing an RTQ system sintered magnet according to the present disclosure includes a crushing step of crushing an RTQ system magnet alloy (R is at least one rare earth element and necessarily includes at least one of Nd and Pr, T is at least one selected from the group consisting of Fe, Co, Ni, Al, Mn, Cr and V, and Q is B and C) to produce an alloy powder, and a step of sintering a compact of the alloy powder to produce an RTQ system sintered magnet. The R content of the RTQ system sintered magnet is 30 mass% or less of the entire RTQ system sintered magnet, the B content of Q is 0.90 mass% or less of the entire RTQ system sintered magnet, and the total content of B and C is 0.99 mass% or less. The pulverization step includes a hydrogen absorbing step in which hydrogen is absorbed in the alloy at a temperature of 200° C. or less in a treatment chamber, and a dehydrogenation step in which hydrogen is exhausted from the treatment chamber and the alloy is dehydrogenated by heating the alloy to a temperature in the range of 80° C. to 350° C. to produce coarsely pulverized powder having a hydrogen content of 1000 ppm to 2000 ppm. The fine pulverization step includes a step of pulverizing the coarsely pulverized powder to obtain fine powder having a median diameter d50 of 3.5 μm or less. Effect of the Invention
[0012] According to the embodiment of the present disclosure, even when the powder particle size is reduced, it is possible to reduce the amount of C. As a result, it is possible to realize an RTQ system sintered magnet in which the amounts of B and C are controlled within the desired ranges and the two-particle grain boundary is modified. [Brief description of the drawings]
[0013] [Figure 1A] FIG. 2 is a schematic diagram showing the main phase and grain boundary phase of an RTB based sintered magnet. [Figure 1B] FIG. 1B is a further enlarged schematic diagram of the dashed rectangular area in FIG. 1A. [Diagram 2] 1 is a flowchart outlining a method for producing an RTQ sintered magnet according to an embodiment of the present disclosure. [Diagram 3] 1 is a table showing compositions of RTQ sintered magnets finally obtained for samples (samples Nos. 1 to 28) in experimental examples of the present disclosure. [Figure 4] 1 is a table showing manufacturing conditions and magnetic properties of samples (samples No. 1 to 28) in experimental examples of the present disclosure. [Diagram 5] 1 is a graph showing the baking temperature dependence of the amount of coarse hydrogen [ppm] in the experimental examples and reference examples of the present disclosure. [Figure 6] 1 is a graph showing the relationship between Br and HcJ for samples in each of Groups I to IV of the experimental examples of the present disclosure. [Figure 7] 1 is a graph showing the relationship between HcJ and B content of samples in each of Groups I to IV of the experimental examples of the present disclosure. [Figure 8] 1 is a graph showing the relationship between HcJ and the (B+C) content of samples in each of Groups I to IV of the experimental examples of the present disclosure. [Figure 9] 1 is a graph showing the relationship between Br and the B content of samples in each of Groups I to IV of the experimental examples of the present disclosure. [Figure 10] 1 is a table showing compositions of RTQ sintered magnets finally obtained for samples (samples Nos. 29 to 38) in experimental examples of the present disclosure. [Figure 11]1 is a table showing manufacturing conditions and magnetic properties of samples (samples Nos. 29 to 38) in experimental examples of the present disclosure. [Figure 12] 1 is a table showing compositions of the RTQ sintered magnets finally obtained from samples (sample Nos. 39 to 49) in experimental examples of the present disclosure. [Figure 13] 1 is a table showing manufacturing conditions and magnetic properties of samples (samples Nos. 39 to 49) in experimental examples of the present disclosure. [Figure 14] 1 is a graph showing the relationship between Br and HcJ for samples in each of Groups VIII and IX of the experimental examples of the present disclosure. [Figure 15] 1 is a graph showing the relationship between HcJ and B content of samples in each of Groups VIII and IX of the experimental examples of the present disclosure. [Figure 16] 1 is a graph showing the relationship between HcJ and the (B+C) content of samples in each of Groups VIII and IX of the experimental examples of the present disclosure. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0014] Conventionally, in RTB sintered magnets, for example, when (1) the content of R (at least one of rare earth elements, which necessarily contains at least one of Nd and Pr) is 27 mass% or more and 34 mass% or less of the entire RTB sintered body, (2) T is at least one selected from the group consisting of Fe, Co, Al, Mn, and Si, T necessarily contains Fe, and the content of Fe in the entire T is 80 mass% or more, and (3) the molar ratio of T to B ([T] / [B]) is more than 14.0 and 15.0 or less, an element such as Ga is added to thicken the two-particle grain boundary and increase the H cJ It is known that it is possible to improve
[0015] The molar ratio of T to B ([T] / [B]) is the ratio (a / b) of the number of moles (a) obtained by dividing the analytical value (mass%) of the concentration of each element (Fe and at least one of Co, Al, Mn, and Si) constituting T by the atomic weight of each element, to the number of moles (b) obtained by dividing the analytical value (mass%) of the concentration of B by the atomic weight of B.
[0016] When the molar ratio of T to B ([T] / [B]) exceeds 14.0, the B content is R2T 14 This means that the ratio of the main phase (R2T 14 The amount of B is reduced relative to the amount of T used to form the compound (B).
[0017] Next, the basic structure of an RTB based sintered magnet will be described.
[0018] RTB sintered magnets have a structure in which powder particles of raw alloys are bonded together by sintering, and are mainly 14 It is composed of a main phase made of B compounds and a grain boundary phase located at the grain boundaries of this main phase.
[0019] FIG. 1A is a schematic diagram showing the main phase and grain boundary phase of an RTB based sintered magnet, and FIG. 1B is a schematic diagram further enlarging the dashed rectangular area in FIG. 1A. In FIG. 1A, an arrow of 5 μm in length is shown as an example for reference, showing the reference length of the size. As shown in FIG. 1A and FIG. 1B, an RTB based sintered magnet is mainly composed of R2T 14 The grain boundary phase 14 is composed of a main phase 12 made of a B compound and a grain boundary phase 14 located at the grain boundary portion of the main phase 12. As shown in FIG. 1B, the grain boundary phase 14 is composed of two R2T 14 B compound grains are adjacent to each other in the two-particle grain boundary phase 14a, and there are three or more R2T 14 The B compound grains include adjacent grain boundary triple junctions 14b.
[0020] R2T, which is main phase 12 14The B compound is a ferromagnetic phase with high saturation magnetization and anisotropic magnetic field. Therefore, in RTB sintered magnets, the R2T 14 By increasing the proportion of B compounds, r It can improve R2T 14 In order to increase the ratio of B compounds, the amounts of R, T, and B in the raw alloy should be adjusted to R2T 14 The best way is to get the stoichiometric ratio of B compound (R amount:T amount:B amount = 2:14:1). 14 When the amount of B or R for forming the B compound is less than the stoichiometric ratio, the grain boundary phase 14 generally contains an Fe phase or an R2T phase. 17 Soft magnetic phases such as H cJ However, the amount of B is reduced by R2T 14 When the amount of B compound is less than the stoichiometric ratio and one or more metal elements M selected from Al, Ga, and Cu are contained, R2T 17 The grain boundaries become thicker due to the formation of transition metal-rich phases (e.g., RT-Ga phases) at the grain boundaries from the phase, resulting in high H cJ can be obtained.
[0021] As mentioned above, in an RTB sintered magnet, in order to thicken the two-particle grain boundary, not only the amount of B but also the amount of carbon (C), which acts similarly to boron (B), is important. According to the inventors' studies, it is not desirable for the amount of carbon (C) contained in an RTB sintered magnet to increase during the manufacturing process of a powder compact obtained by pulverizing the raw material magnet alloy.
[0022] <Embodiment> Next, an embodiment of a method for producing an RTQ sintered magnet according to the present disclosure will be described.
[0023] First, the method for producing an RTQ sintered magnet of this embodiment will be outlined with reference to FIG.
[0024] As shown in Fig. 2, the method for producing an RTQ system sintered magnet in this embodiment includes a pulverization step S100 of pulverizing an RTQ system magnet alloy to produce an alloy powder, a powder compaction step S200 of producing a compact of the alloy powder, and a sintering step S300 of sintering the compact to produce an RTQ system sintered magnet. Here, R is at least one rare earth element and always includes at least one of Nd and Pr. T is at least one element selected from the group consisting of e, Co, Ni, Al, Mn, Cr, and V, and always includes Fe. Q is B and C. The R content of the RTQ system sintered magnet is 30 mass% or less of the entire RTQ system sintered magnet. The B content is 0.90 mass% or less of the entire RTQ system sintered magnet, and the total content of B and C is 0.99 mass% or less. Preferably, the B content is 0.80 mass% or more and 0.90 mass% or less of the entire RTQ sintered magnet, and the total content of B and C is 0.85 mass% or more and 0.99 mass% or less. By setting the R content of the RTQ sintered magnet to 30 mass% or less of the entire RTQ sintered magnet, and keeping the B content and the total content of B and C within the ranges of the present disclosure, it is possible to prevent the formation of R6T at the grain boundaries of the RTQ sintered magnet. 13 Ga is formed, the grain boundary becomes thick, and the B r and high H exceeding 1640kA / m cJ In order to make the two-particle grain boundary thicker, it is more preferable that the molar ratio of T ([T] / [B]) is more than 14.0 and not more than 15.0. The raw material alloy is produced, for example, by a strip casting method. By having such a composition, the above-mentioned two-particle grain boundary is thickened, and high H cJ It is possible to obtain the effect of realizing the above.
[0025] The pulverization step S100 includes a hydrogen pulverization step S10 and a fine pulverization step S20.
[0026] The hydrogen pulverization process S10 includes a hydrogen absorption process S12 in which hydrogen is absorbed into the above-mentioned alloy at a temperature of 200°C or less in a treatment chamber, and a dehydrogenation process S14 in which hydrogen is exhausted from the treatment chamber and the alloy is heated to a temperature in the range of 80°C to 350°C to perform a dehydrogenation process, thereby producing a coarsely pulverized powder having a hydrogen content of 1000 ppm to 2000 ppm by mass.
[0027] In the embodiment of the present disclosure, it is important to adjust the hydrogen content of the coarsely pulverized powder to 1000 ppm or more and 2000 ppm or less by setting the hydrogen absorption temperature to 200°C or less in this hydrogen pulverization step S10. As shown in the examples described later, when the hydrogen content of the coarsely pulverized powder is in the range of 1000 ppm or more and 2000 ppm or less, even if the particle size of the powder (finely pulverized powder) obtained in the next fine pulverization step S20 is reduced, the effect of suppressing the increase in the carbon concentration in the finally obtained sintered magnet can be obtained. The hydrogen content is preferably 1000 ppm or more and 1800 ppm or less.
[0028] The fine pulverization step S20 includes a step of pulverizing the coarsely pulverized powder to obtain a fine powder having a median diameter d50 of 3.5 μm or less. The fine pulverization step may include a step of mixing an organic grinding aid with the coarsely pulverized powder. An example of an organic grinding aid is zinc stearate. The median diameter d50 of the fine powder is preferably 2.0 μm or more and 3.5 μm or less, and more preferably 2.0 μm or more and 3.0 μm or less. Here, the median diameter d50 is the central value of the volume frequency obtained by measurement using an airflow dispersion type laser diffraction method. More specifically, the median diameter d50 in the embodiment of the present disclosure is measured using a particle size distribution measuring device "HELOS&RODOS" manufactured by Sympatec. Dispersion pressure: 4bar Measurement range: R2 Calculation mode: HRLD In the fine pulverization step S20, the median diameter d50 can be pulverized to 3.5 μm or less, preferably 3.3 μm or less (e.g., 3.0 μm or less) using, for example, a jet mill. However, it is very difficult to reduce the median diameter d50 of the alloy powder to less than 2.0 μm, and this is not preferred because it would result in a significant decrease in production efficiency.
[0029] After obtaining a powder having a median diameter d50 of 3.5 μm or less in this way, in the powder compacting step S200, the powder is oriented in a magnetic field, for example, to produce a compact of the alloy powder. In the sintering step S300, the powder compact is sintered to produce an RTQ sintered magnet. The sintering temperature for the compact is, for example, 900° C. or higher and 1100° C. or lower. The contents of the powder compacting step S200 and the sintering step S300 are not particularly limited, and may be performed, for example, by a known method.
[0030] It is not clear why adjusting the hydrogen content of the coarsely pulverized powder to the range of 1000 ppm to 2000 ppm can suppress an increase in the carbon concentration in the final RTQ sintered magnet. The inventors believe that this is because hydrogen in the powder particles heated during the sintering process combines with carbon in organic substances such as the lubricant contained in the powder compact to generate volatile components that are more likely to volatilize.
[0031] Conventionally, it has been thought that the lower the hydrogen content of powder particles, the better. This is because it has been observed that if the powder particles contain a large amount of hydrogen, the hydrogen released during the sintering process is reabsorbed into the sintered body, causing the sintered body to expand, resulting in cracking of the sintered body. However, according to the experiments of the present invention, when powder particles having the above composition range and a relatively small particle size are used, such cracking of the sintered body was not observed as long as the hydrogen content of the coarsely pulverized powder was in the range of 1000 ppm to 2000 ppm. Also, if the hydrogen content is less than 1000 ppm, the carbon content in the finally obtained sintered magnet cannot be reduced.
[0032] According to the embodiment of the present disclosure, even if the total content of Dy and Tb in the RTQ system sintered magnet is 0.5 mass% or less (including 0 mass%), B r ≧1.39T,H cJ It is possible to achieve excellent magnetic properties of ≧1640kA / m.
[0033] Various elements may be diffused from the surface to the inside of the RTQ sintered magnet produced by the above process. This can improve the magnetic properties. In this case, the magnet may be called the "sintered material" before diffusion.
[0034] The sintered body material may be produced from one type of raw material alloy (single raw material alloy), or may be produced by using two or more types of raw material alloys and mixing them (blending method). The obtained sintered body material may be subjected to a known mechanical processing such as cutting or machining as necessary, and then to a first heat treatment and a second heat treatment described later.
[0035] In this embodiment, at least one of Nd and Pr may be diffused from the surface to the inside of the sintered body material obtained by the above method. As a result of such diffusion, the RTQ sintered magnet includes a portion where at least one of the Nd concentration and the Pr concentration gradually decreases from the magnet surface to the magnet interior. Similarly, at least one of the Tb concentration and the Dy concentration may be diffused from the magnet surface to the magnet interior. As a result of such diffusion, the RTQ sintered magnet includes a portion where at least one of the Tb concentration and the Dy concentration gradually decreases from the magnet surface to the magnet interior.
[0036] A process for preparing a diffusion source First, the composition of the diffusion source in the step of preparing the diffusion source will be described.
[0037] The diffusion source may be composed of heavy rare earth elements such as Dy, Tb, Gd, and Ho. Preferably, the rare earth elements include at least one of Nd and Pr. It is preferable that 50 mass% or more of the rare earth elements is Pr. It is possible to obtain a higher H while suppressing the content of valuable heavy rare earth elements. cJ According to the present disclosure, it is possible to obtain a sufficiently high H cJ Therefore, the content of the heavy rare earth element is preferably 10 mass% or less of the entire diffusion source, more preferably 5 mass% or less, and further preferably none (substantially 0 mass%). Even when the diffusion source contains a heavy rare earth element, it is preferable that 50% or more of the rare earth element is Pr, and it is more preferable that the rare earth element excluding the heavy rare earth element is only Pr (including unavoidable impurities).
[0038] When at least one of Nd and Pr is necessarily contained as a rare earth element, the content is preferably, for example, 35 mass% or more and less than 85 mass% of the entire diffusion source. If the content of the rare earth element is less than 35 mass%, the diffusion may not proceed sufficiently in the first heat treatment described later. On the other hand, if the content of the rare earth element is 85 mass% or more, the alloy powder becomes very active during the manufacturing process of the diffusion source. As a result, the alloy powder may be significantly oxidized or ignited.
[0039] In addition to the above elements, the diffusion source may contain Ga, Fe, Cu, Co, Al, Ag, Zn, Si, In, Sn, Zr, Nb, Ti, Ni, Hf, Ta, W, Ge, Mo, V, Y, La, Ce, Sm, Ca, Mg, Mn, Cr, H, F, P, S, Cl, O, N, C, etc.
[0040] The diffusion source can be prepared by a method for producing a raw material alloy that is employed in a general manufacturing method typified by Nd-Fe-M sintered magnets, such as a die casting method, a strip casting method, a single roll super-quenching method (melt spinning method), or an atomizing method. The diffusion source may also be an alloy obtained by the above method, which has been pulverized by a known pulverizing means such as a pin mill. In order to improve the pulverizability of the alloy obtained by the above method, the alloy may be heat-treated in a hydrogen atmosphere at 700°C or less to incorporate hydrogen, and then pulverized.
[0041] A process in which elements contained in the diffusion source are diffused from the surface of the sintered body to the inside. By performing heat treatment at a temperature of 700°C or higher and 1100°C or lower in a vacuum or inert gas atmosphere, the elements contained in the diffusion source are diffused from the surface of the sintered body to the inside. In the present disclosure, this heat treatment is referred to as the first heat treatment. If the heat treatment temperature for diffusion is less than 700°C, the diffusion is insufficient and a high H cJ On the other hand, if the temperature exceeds 1100℃, abnormal grain growth of the main phase occurs, and H cJ The heat treatment temperature for diffusion is preferably 800°C or higher and 1000°C or lower. cJ This is because it is possible to obtain the above. The heat treatment time is set to an appropriate value depending on the composition and dimensions of the sintered body material and the diffusion source, the heat treatment temperature, etc., but is preferably 5 minutes to 30 hours, more preferably 10 minutes to 25 hours, and even more preferably 30 minutes to 20 hours. It is also preferable to prepare the diffusion source in an amount of 1 mass% to 30 mass% of the weight of the sintered body material. If the diffusion source is less than 1 mass% of the weight of the sintered body material, H cJ On the other hand, if it exceeds 30 mass%, B r may decrease.
[0042] The heat treatment for diffusion can be performed using a known heat treatment method. For example, the surface of the sintered body material can be covered with a powder layer of the diffusion source, and the first heat treatment can be performed. For example, the diffusion source can be coated on the surface of the sintered body material by a sputtering method, and then the first heat treatment can be performed. For example, a slurry in which the diffusion source is dispersed in a dispersion medium can be applied to the surface of the sintered body material, and the dispersion medium can be evaporated to bring the diffusion source into contact with the sintered body material. Examples of the dispersion medium include alcohol (ethanol, etc.), NMP (N-methylpyrrolidone), aldehydes, and ketones. In addition, the sintered body material that has been subjected to the first heat treatment can be subjected to known mechanical processing such as cutting or machining.
[0043] The sintered body material that has been subjected to the heat treatment for diffusion may be subjected to a heat treatment at a temperature of 450° C. or more and 600° C. or less in a vacuum or in an inert gas atmosphere. In the present disclosure, this heat treatment is referred to as a second heat treatment. By performing the second heat treatment, a high B r and high H cJ By setting the temperature of the second heat treatment to 450° C. or more and 600° C. or less, R6T 13 The formation of the Ga phase progresses. The second heat treatment temperature is preferably 480°C or higher and 560°C or lower. cJ The heat treatment time is set to an appropriate value depending on the composition and dimensions of the sintered body material, the heat treatment temperature, etc., and is preferably from 5 minutes to 20 hours, more preferably from 10 minutes to 15 hours, and even more preferably from 30 minutes to 10 hours. EXAMPLES
[0044] The present disclosure will be described in more detail below with reference to experimental examples (including examples and comparative examples); however, the present disclosure is not limited thereto.
[0045] The table in FIG. 3 shows the composition of the RTQ sintered magnets finally obtained from the samples (samples No. 1 to 28) in this experimental example. The column "Sample" in the table in FIG. 3 lists 28 sample numbers divided into five groups I to V. The composition (mass%) of the RTQ sintered magnet is listed for each sample. The composition of the RTQ sintered magnet samples obtained by carrying out the manufacturing method described below was analyzed by ICP (inductively coupled plasma) optical emission spectroscopy to determine the content of Fe, Nd, Pr, Dy, B, Co, Al, Cu, Ga, and Zr, the amount of H by a gas analyzer "EMGA-930" manufactured by Horiba, Ltd., the amount of O and the amount of N by a gas analyzer "EMGA-920", and the amount of C by a gas analyzer "EMIA-920V2 / FA". In addition, "TRE" shown in the table in FIG. 3 is the total composition of the rare earth alloy, and "B+C" is the total composition of boron (B) and carbon (C).
[0046] Each sample was obtained by the following steps.
[0047] First, flake-shaped alloys for RTB sintered magnets were produced by strip casting. The alloys for RTB sintered magnets were obtained by melting various raw material alloys and then cooling and solidifying them to achieve the compositions shown in the table in Figure 3.
[0048] The obtained alloy flakes were placed in the treatment chamber of a hydrogen crushing device, where a hydrogen absorption process was carried out in a pressurized hydrogen atmosphere. The hydrogen absorption process was carried out at a temperature of 200°C or less, specifically at 80°C. The alloy absorbed hydrogen and became embrittled as a result of the hydrogen absorption process.
[0049] Next, hydrogen was evacuated from the treatment chamber, and the samples were heated (baked) to a predetermined temperature in a vacuum, and then cooled for dehydrogenation to obtain coarsely pulverized powder. The baking temperature for the dehydrogenation was set to a different value for each of groups I to IV, as shown in the table of FIG. 4. Specifically, the baking temperatures for groups I, II, III, and IV were 550°C, 350°C, 190°C, and 150°C, respectively. For group V, heating (baking) for the dehydrogenation was not performed.
[0050] The amount of hydrogen contained in the coarsely pulverized powder of each sample thus obtained (coarse hydrogen amount) was measured using a gas analyzer "EMGA-930" manufactured by Horiba, Ltd. The measured values of the coarse hydrogen amount are shown in the table of Figure 4. The unit of the coarse hydrogen amount in this application is ppm (parts per million) based on mass.
[0051] Figure 5 is a graph showing the baking temperature dependence of the amount of coarse hydrogen [ppm]. In the graph of Figure 5, the baking temperature dependence of the amount of coarse hydrogen [ppm] is also shown by the dotted line and the dashed line for the reference examples in which the total composition TRE of rare earth elements is 36 mass% and 32.9 mass%, respectively.
[0052] As can be seen from Fig. 5, the lower the baking temperature, the more the amount of coarse hydrogen increases. In addition, the amount of coarse hydrogen when the total composition TRE of rare earth elements is 30 mass% or less can have a low value that is not realized when the total composition TRE of rare earth elements exceeds 30 mass%. According to the embodiment of the present disclosure, since the total composition TRE of rare earth elements is 30 mass% or less, the amount of coarse hydrogen can be controlled to a range of 1000 ppm or more and 200 ppm or less by adjusting the baking temperature in the range of 80 ° C. or more and 350 ° C. or less.
[0053] The coarsely pulverized powder and zinc stearate were mixed and fed into an airflow pulverizer (jet mill device) to obtain finely pulverized powder. Specifically, finely pulverized powder with a median diameter d50 of 3.5 μm was obtained. Methyl caprylate was added to the finely pulverized powder, which was then immersed in normal dodecane to prepare a slurry. The obtained slurry was molded in a magnetic field (wet molding) to obtain a compact. The molding device used was a so-called perpendicular magnetic field molding device (horizontal magnetic field molding device), in which the magnetic field application direction and the pressure direction are perpendicular to each other.
[0054] The obtained compacts were subjected to a sintering process in which they were held in a vacuum at the sintering temperature shown in the table of Fig. 4 for about 5 hours to obtain sintered compacts. As shown in the table of Fig. 4, the density of each of the sintered compacts was 77.5 × 10 3 kg / m3 (=7.5g / cm 3) That was all.
[0055] The sintered body was heat-treated in a vacuum at 800°C for 2 hours, and then machined into a cube with a side length of 7.2 mm. The machined cube sample was then heat-treated at 500°C for 2 hours, after which the six faces of the cube sample were ground to machine it into a cube with a side length of 7 mm. The residual magnetic flux density B r and coercive force H cJ The magnetic properties of the samples in group V were not measured because they were all broken. r [T], H cJ [kA / m] are shown in the table in Figure 4.
[0056] As shown in the tables of Figures 3 and 4, in Samples Nos. 10 to 12, 15 to 18, and 21 to 23, which are examples of the present invention, the C content was kept low, the B content was 0.90 mass% or less of the entire RTQ sintered magnet, and the total content of B and C was 0.99 mass% or less. In all of these Samples Nos. 10 to 12, 15 to 18, and 21 to 23, the total content of Dy and Tb in the RTQ sintered magnet was 0.5 mass% or less (including 0 mass%), and the B r ≧1.39T,H cJ It was possible to demonstrate excellent magnetic properties of ≧1640kA / m.
[0057] Figure 6 shows the B r and H cJ FIG. 7 is a graph showing the relationship between H cJ FIG. 8 is a graph showing the relationship between the H content and the B content. cJ 9 is a graph showing the relationship between the content of (B+C) and the content of B. rand the B content. In these graphs, the data for Group I (samples No. 1 to 6) are shown as squares, the data for Group II (samples No. 7 to 12) are shown as circles, the data for Group III (samples No. 13 to 18) are shown as diamonds, and the data for Group IV (samples No. 19 to 23) are shown as triangles.
[0058] As can be seen from Figure 6, in Group I with a baking temperature of 500°C, the B r can be obtained, but the relatively high H cJ It is difficult to obtain the above. Also, as can be seen from Figures 7 and 8, in Group I, the total content of B and C tends to increase compared to other groups because the C content is increased. Furthermore, as can be seen from Figure 9, when the B content is the same, when the baking temperature is lowered, that is, when the coarse powder hydrogen content increases, the B content tends to increase. r Therefore, the baking temperature is preferably, for example, 100° C. or higher.
[0059] Next, similar experimental examples were prepared by changing the particle size of the finely pulverized powder (fine powder). The main differences from the previous experimental examples were in the baking temperature and the fine pulverization process. For samples No. 29 to No. 33 in group VI in the table of FIG. 10, the baking temperature was set to 150°C, and in the fine pulverization process, pulverization was performed so that the median diameter d50 was 3.3 μm. In contrast, for samples No. 34 to No. 38 in group VII in the table of FIG. 10, the baking temperature was set to 150°C, and in the fine pulverization process, pulverization was performed so that the median diameter d50 was 3.6 μm.
[0060] As can be seen from Fig. 11, when the median diameter d50 is 3.6 μm, which is greater than 3.5 μm (Group VII), B r ≧1.39T was achieved, but H cJ ≧1640kA / m could not be achieved.
[0061] Next, a similar experiment was made by further reducing the particle size of the finely pulverized powder (fine powder). The main differences from the previous experiment are the baking temperature for the dehydrogenation treatment, the median diameter d50 of the fine powder produced in the fine pulverization process, and the Dy content of the RTQ sintered magnet being 0.3 mass%. The alloy for the RTB sintered magnet was obtained by melting various raw alloys so as to realize the composition shown in the table of FIG. 12, and then cooling and solidifying them. For samples No. 39 to 44 of group VIII in the table of FIG. 12, the baking temperature was set to 100°C, and in the fine pulverization process, the pulverization was performed so that the median diameter d50 was 2.7 μm. In contrast, for samples No. 45 to 49 of group IX in the table of FIG. 12, the baking temperature was set to 500°C, and in the fine pulverization process, the pulverization was performed so that the median diameter d50 was 2.7 μm.
[0062] Theoretically, the smaller the median diameter d50 of the fine powder, the cJ However, in reality, as the median diameter d50 becomes smaller, the surface area per unit volume of each powder particle that constitutes the fine powder increases, and the H cJ It is difficult to realize an increase in the total content of B and C during the manufacturing process. In addition, if the surface area per unit volume of each powder particle constituting the fine powder increases, the C content is likely to increase during the manufacturing process. For this reason, if the median diameter d50 of the fine powder becomes, for example, 3.0 μm or less, it is considered difficult to adjust the total content of B and C to 0.99 mass% or less.
[0063] As a result of this experiment, in the case of samples No. 41 to No. 44 (Group VIII) where the baking temperature was 100°C and the median diameter d50 was 2.7 μm, as can be seen from FIG. 13, a high value H of 1700 kA / m or more was achieved while maintaining Br ≧ 1.30 T. cJ As shown in Fig. 12, the total content of B and C in Samples Nos. 41 to 44 was 0.99 mass% or less, whereas the total content of B and C in Samples Nos. 39 to 40 exceeded 0.99 mass%.
[0064] On the other hand, in the case of samples No. 45 to 49 in which the baking temperature was 500°C and the median diameter d50 was 2.7 μm (Group IX), as can be seen from FIG. 13, the amount of coarse hydrogen was significantly lower than 1000 ppm, and H cJ Even if the RTQ sintered magnet contains 0.3 mass% Dy, cJ The total content of B and C in all of Samples No. 45 to No. 49 in Group IX exceeded 0.99 mass%, as shown in FIG.
[0065] FIG. 14 shows the B of samples in groups VIII and IX. r and H cJ FIG. 15 is a graph showing the relationship between H cJ FIG. 16 is a graph showing the relationship between the H content and the B content. cJ 4A and 4B are graphs showing the relationship between the (B+C) content and the data for Group VIII (samples No. 39-44) are shown as white diamonds, and the data for Group IX (samples No. 45-49) are shown as white circles.
[0066] As can be seen from FIG. 14, in group VIII, where the median diameter d50 is small at 2.7 μm and the baking temperature is 100°C, the high H cJ Specifically, in group VIII, samples No. 41 to No. 44, in which the total content of B and C is 0.99 mass% or less, exhibited a high H cJ was able to achieve.
[0067] 15 and 16, in Group VIII (Samples Nos. 39 to 44) where the baking temperature was 100°C, the increase in the C content was suppressed and a low total content of B and C of 0.99 mass% or less was achieved compared to Group IX (Samples Nos. 45 to 49) where the baking temperature was 500°C. In general, it is believed that the smaller the median diameter d50, the greater the surface area of the fine powder, making it easier for the C content to increase during the manufacturing process. For this reason, it can be said that the effect of suppressing the increase in the C content according to the present invention is particularly remarkable when manufacturing RTQ sintered magnets using fine powder with a median diameter d50 of 3.0 μm or less.
[0068] From this experimental example, even when producing fine powder with a median diameter d50 of 3.0 μm or less (for example, 2.6 to 2.8 μm), by adjusting the baking temperature in the hydrogen crushing process to produce coarsely crushed powder with a hydrogen content of 1000 ppm to 2000 ppm, it is easy to keep the total content of B and C within the desired range, so that a higher H cJ It is clear that this can be achieved.
[0069] As described above, the present disclosure includes the methods for producing RTQ based sintered magnets described in the following items.
[0070] [Item 1] a crushing step of crushing an RTQ magnet alloy (R is at least one rare earth element and necessarily contains at least one of Nd and Pr, T is Fe or Fe and Co, and is at least one element selected from the group consisting of Fe, Co, Ni, Al, Mn, Cr and V, and Q is B and C) to produce an alloy powder; a powder compacting step of producing a compact of the alloy powder; a sintering step of sintering the compact to produce an RTQ based sintered magnet; Including, the R content of the RTQ system sintered magnet is 30 mass% or less of the entire RTQ system sintered magnet, the B content is 0.90 mass% or less of the entire RTQ system sintered magnet, and the total content of B and C is 0.99 mass% or less, The pulverization step includes a hydrogen pulverization step and a fine pulverization step, The hydrogen pulverization step comprises: a hydrogen absorption step of absorbing hydrogen into the alloy at a temperature of 200° C. or less in a treatment chamber; a dehydrogenation process in which hydrogen is exhausted from the treatment chamber and the alloy is dehydrogenated by heating the alloy to a temperature in the range of 80° C. to 350° C. to produce a coarsely pulverized powder having a hydrogen content of 1000 ppm to 2000 ppm; Including, The fine pulverization step includes a step of pulverizing the coarsely pulverized powder to obtain fine powder having a median diameter d50 of 3.5 μm or less.
[0071] [Item 2] 2. The method for producing an RTQ sintered magnet according to item 1, wherein the hydrogen content is 1000 ppm or more and 1800 ppm or less.
[0072] [Item 3] the total content of Dy and Tb in the RTQ sintered magnet is 0.5 mass% or less (including 0 mass%), Br≧1.39T HcJ≧1640kA / m 3. The method for producing an RTQ system sintered magnet according to item 1 or 2,
[0073] [Item 4] 4. The method for producing an RTQ system sintered magnet according to any one of items 1 to 3, wherein the fine pulverization step includes a step of pulverizing the coarsely pulverized powder to obtain a fine powder having a median diameter d50 of 3.3 μm or less.
[0074] [Item 5] 5. The method for producing an RTQ system sintered magnet according to any one of items 1 to 4, wherein the fine pulverization step includes a step of mixing an organic pulverization aid with the coarsely pulverized powder.
[0075] [Item 6] 6. The method for producing an RTQ system sintered magnet according to any one of items 1 to 5, wherein the powder compacting step is carried out by a wet compacting method.
[0076] [Item 7] 7. The method for producing a RTQ system sintered magnet according to any one of items 1 to 6, wherein the fine pulverization step is carried out using a jet mill.
[0077] [Item 8] the RTQ system sintered magnet contains at least one of Dy and Tb, the total content of Dy and Tb being more than 0 mass% and not more than 0.5 mass%, Br≧1.30T H cJ ≧1700kA / m 8. The method for producing an RTQ system sintered magnet according to any one of items 1 to 7,
[0078] [Item 9] 9. The method for producing a RTQ system sintered magnet according to any one of items 1 to 8, wherein the fine pulverization step includes a step of pulverizing the coarsely pulverized powder to obtain a fine powder having a median diameter d50 of 3.0 μm or less. [Explanation of symbols]
[0079] 12 Main phase 14 Grain boundary phase 14a Two-grain grain boundary phase 14b Grain boundary triple point
Claims
1. a pulverization step of pulverizing an R-T-Q magnet alloy (R is at least one rare earth element and necessarily includes at least one of Nd and Pr, T is at least one element selected from the group consisting of Fe, Co, Ni, Al, Mn, Cr and V and necessarily includes Fe, and Q is B and C) to produce an alloy powder; a powder compacting step of producing a compact of the alloy powder; a sintering step of sintering the compact to produce an R-T-Q based sintered magnet; Including, the R content of the R-T-Q based sintered magnet is 30 mass% or less of the entire R-T-Q based sintered magnet, the B content is 0.90 mass% or less of the entire R-T-Q based sintered magnet, and the total content of B and C is 0.99 mass% or less, The pulverization step includes a hydrogen pulverization step and a fine pulverization step, The hydrogen pulverization step comprises: a hydrogen absorption step of absorbing hydrogen into the R-T-Q type magnet alloy at a temperature of 200° C. or less in a treatment chamber; a dehydrogenation process in which hydrogen is exhausted from the treatment chamber and the alloy is dehydrogenated by heating the alloy to a temperature in the range of 80° C. to 350° C. to produce a coarsely pulverized powder having a hydrogen content of 1000 ppm to 2000 ppm; Including, The fine pulverization step includes a step of pulverizing the coarsely pulverized powder to obtain fine powder having a median diameter d50 of 3.5 μm or less.
2. 2. The method for producing an R-T-Q sintered magnet according to claim 1, wherein the hydrogen content is from 1000 ppm to 1800 ppm.
3. the total content of Dy and Tb in the R-T-Q based sintered magnet is 0.5 mass% or less (including 0 mass%), <h2 style=";text-align:left;direction:ltr">B<h2 style=";text-align:left;direction:ltr"> r <h2 style=";text-align:left;direction:ltr"> ≧1535T H cJ ≧1640kA / m The method for producing an R-T-Q sintered magnet according to claim 1,
4. The method for producing an R-T-Q system sintered magnet according to claim 1 , wherein the fine pulverization step includes a step of pulverizing the coarsely pulverized powder to obtain a fine powder having a median diameter d50 of 3.3 μm or less.
5. 4. The method for producing an R-T-Q system sintered magnet according to claim 1, wherein the fine pulverization step includes a step of mixing an organic pulverization aid with the coarsely pulverized powder.
6. The method for producing an R-T-Q system sintered magnet according to claim 1, wherein the powder compacting step is carried out by a wet compacting method.
7. The method for producing an R-T-Q sintered magnet according to claim 1, wherein the fine pulverization step is carried out using a jet mill.
Citation Information
Patent Citations
Dehydrogenation treatment furnace for r-t-b based alloy for antisotropic bonded magnet
JP2003342601A
METHOD FOR MANUFACTURING Nd-Fe-B BASED SINTERED MAGNETIC MATERIAL
JP2021077868A
Sintered body for forming rare-earth magnet and rare-earth sintered magnet
JP2021106271A
Manufacturing method of r-t-b system sintered magnet and r-t-b system sintered magnet
JP2022151483A
R-t-b sintered magnet
WO2008139556A1
